2015
DOI: 10.1371/journal.pone.0118411
|View full text |Cite
|
Sign up to set email alerts
|

Association between Appendectomy and Subsequent Colorectal Cancer Development: An Asian Population Study

Abstract: ObjectivesThe appendix may modulate colon microbiota and bowel inflammation. We investigated whether appendectomy alters colorectal cancer risk.MethodsWe identified a cohort of 75979 patients who underwent appendectomy between 1997 and 1999 based on the insurance claims of Taiwan. A comparison cohort of 303640 persons without appendectomy was selected randomly, frequency matched by age, sex, comorbidity and entry year was also selected. We monitored subsequent colorectal cancer development in both cohorts.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 68 publications
8
99
1
2
Order By: Relevance
“…By removal of the appendix, however, we are removing an immune organ and potentially a reservoir of beneficial microbiota. This may predispose to subsequent development of other pathologies, such as recurrent Clostridium difficile infection,52 Crohn’s disease53 and colorectal cancer,54 although this is a controversial area and it is difficult to dissect appendicitis from appendectomy and to control for diagnostic uncertainty.…”
Section: Improving the Evidence Base: What We Need To Knowmentioning
confidence: 99%
“…By removal of the appendix, however, we are removing an immune organ and potentially a reservoir of beneficial microbiota. This may predispose to subsequent development of other pathologies, such as recurrent Clostridium difficile infection,52 Crohn’s disease53 and colorectal cancer,54 although this is a controversial area and it is difficult to dissect appendicitis from appendectomy and to control for diagnostic uncertainty.…”
Section: Improving the Evidence Base: What We Need To Knowmentioning
confidence: 99%
“…Previous studies examining the association between appendicitis or appendectomy and risk for neoplastic disease have reported contradictory results (19)(20)(21)(22). To our knowledge only two previous studies have addressed the association between appendicitis or appendectomy and prostate cancer risk, none of which reported a significant association.…”
Section: Discussionmentioning
confidence: 88%
“…17 The microbiota in the large bowel can change after appendectomy, leading to dysbiosis. 9 Gut dysbiosis and inflammation are underlying and linking factors between CKD and DM. 18 Appendectomy could worsen pre-existing dysbiosis in diabetic patients, increasing the risk of ESRD development.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, studies have shown that appendectomy-related impairment of the microbiota may lead to dysbiosis and induce various diseases, including ulcerative colitis, Crohn's disease, Clostridium difficile infection, colorectal cancer, rheumatoid arthritis, and cardiovascular disease. [6][7][8][9] To date, there is no evidence confirming that appendectomy contributes to CKD. In this study, we evaluated the correlation between prior appendectomy and the occurrence of CKD and ESRD.…”
Section: Introductionmentioning
confidence: 99%